Экономические инструменты управления маркетинговым ценообразованием на инновационную продукцию - Перерва, Петр Григорьевич; Долина, Ирина Владимировна; Борзенко, Владимир Иванович; Маслак, Мария Владимировна; Косенко, Андрей Васильевич (Національний технічний університет "Харківський політехнічний інститут", 2020)
В статье обобщены и систематизированы основные факторы ценообразования на рынке инноваций. В процессе исследования выявлены основные ценообразующие факторы, отражающие специфику формирования цены на инновации. Рассмотрены основные возможные методологические подходы к оценке стоимости инноваций.

The article summarizes and systematizes the main factors in the innovation market, taking info account the characterics of the product ''innovation'' as an object of production consumption, on the one hand, and on the other hand, as equivalent of monopoly rights and privileges provided to its owner. In the course of the study, the main pricing factors were identified, reflecting the specifics of price formation for innovations/
Economic tools for management of marketing price for innovative products
Keywords: экономика; менеджмент; цена; маркетинг; коммерциализация; инновационная продукция; economics; management; price; marketing; commercialization; innovative products